Teaching and Learning from Within : a core reflection approach to quality and inspiration in education - Korthagen, Fred A. J., 1949-; Kim, Younghee M.; Greene, William L. (New York : Routledge, 2013)
"Teaching and Learning from Within brings together theory, research, and practice on core reflection, an approach that focuses on people's strengths as the springboard for personal growth and serves every human being involved in education, including students, teachers, school principals, and university faculty. This approach supports the essential role of authenticity in the development of the whole person. It has been used in contexts around the world and has shown great promise in helping to re-chart the course for education and to re-think its purpose in global and democratic societies. The book looks at the current educational context and the need for core reflection; introduces the theory and its linkages to previous studies in numerous disciplines; presents various applications in multinational research and practice with teachers, with students and schools, and with teacher educators; and highlights ongoing work in around the world along with future plans, opportunities, and resources for professional development and research."--
Includes bibliographical references and index.
Keywords: Reflective teaching; Reflective learning; Holistic education; Motivation in education